IMPLEMENTASI ALGORITMA DIJKSTRA DAN METODE HAVERSINE PADA PENENTUAN JALUR TERPENDEK PENDAKIAN GUNUNG MERAPI JALUR SELO BERBASIS ANDROID - Roddy Yoto Sumaryo; Paulus Harsadi; Didik Nugroho (Jurnal Teknologi Informasi dan Komunikasi (TIKomSiN), 2020)
Mount Climbing or mountaineering is one of high-risk sports having certain techniques. There are many factors emerging the lost of mountaineer, such as, getting lost or having out of the track because of bad weather and trying for a new track without well-preparations. Meanwhile, the information of mountaineering route usually can be got from brochure or map at mount base camp in general. Furthermore, some cases state that the mountaineers also must find the closest path to the peak or the closest base camp because of bad weather or condition. The lack of mountain cartographic application and the importance of the closest track become the background of the Dijkstra algorithm implementation based on Android for deciding the shortest track to Mount Merapi via Selo. The methods of this research are Dijkstra algorithm for deciding the shortest rate and Harversine method for giving the value of passed node. The use of Google map and GPS applications are used for mapping and finding the location coordinate. This data will be processed using PHP and MySql database. The results of research are this application can be used easily using smartphone and the feasibility test shows “Good” value with 77% average.